The influences of employee engagement at Bangunan Tun Haji Abdul Razak, Kangar, Perlis / Nur Shawana Samsudin - Samsudin, Nur Shawana (2015)
This study focused on the influences of employee engagement. The objectives of this study are to analyse the relationship between work environment, leadership, team and co-worker and training and career development with employee engagement. The respondents for this study is 120 employees who work at Bangunan Tun Haji Abdul Razak, Kangar. The data that gathered from the respondents using simple random sampling technique. Statistical Package for Social Science (SPSS) version 19 was used to analyse the data and the results does not support four hypotheses in this study. The results revealed that R square = which indicated that % of varience that explained the employee engagement was accounted by work environment, leadership, team and co-worker and training and career development. For the recommendations, I has suggested that the organization should concern more on work environment and always give training to the employee in order to improve employees' skills. Furthermore, the organization also should provide leadership training program that focus on leader and the employees that may be can be leaders in the future.